Effectiveness of a modified double-trap mosquito device with rice straw infusion attractant in increasing ovitrap and gravidtrap indices - Alsya Latisa; Rosa Nur Munawaroh; Sri Nuraeni; Mela Nurfadila; Rochmanah Suhartati; Rudy Hidana; Tanendri Arrizqiyani; Dewi Peti Virgianty; Dina Ferdiani (Journal of Indonesian Medical Laboratory and Science, 2026)
The modified double-trap mosquito device combines ovitrap and gravidtrap functions in a single container to capture mosquito eggs and gravid adults, with application for Aedes aegypti surveillance in dengue-endemic households. This study assessed whether adding a 0.83% rice straw infusion attractant improved the ovitrap index (OI), gravidtrap index (GI), and trap catches compared with a control device. An experiment was conducted in 100 houses in Kampung Sindangsuka, Gunung Gede Village, Kawalu District, Tasikmalaya City, from 14 to 27 April 2024. Each house received one modified device and one control device, yielding 100 per group. Traps were placed in humid, low-light indoor locations and monitored for two weeks. Mosquito eggs and adults were counted, although specimens were not identified to species level. OI and GI were calculated as percentages of positive traps, while egg and adult counts were compared using the Mann–Whitney U test after normality assessment. The modified device achieved higher OI and GI values than the control, with an OI of 62% versus 12% and a GI of 52% versus 23%. It collected 8,002 eggs, averaging 80.02 eggs per device and representing 91% of all eggs, and 94 adult mosquitoes, averaging 0.94 per device and representing 72% of all adults. The control collected 746 eggs and 36 adults. Differences in egg and adult catches were significant (p < 0.001). These findings indicate that 0.83% rice straw infusion enhances trap attractiveness and detection capacity, supporting its use as a low-cost tool for Aedes surveillance and community-based dengue vector control.